Genetic heterogeneity of polymicrogyria: study of 123 patients using deep sequencing. Issue 1 (26th December 2020) - Stutterd, Chloe A; Brock, Stefanie; Stouffs, Katrien; Fanjul-Fernandez, Miriam; Lockhart, Paul J; McGillivray, George; Mandelstam, Simone; Pope, Kate; Delatycki, Martin B; Jansen, Anna; Leventer, Richard J
Abstract: Polymicrogyria is a malformation of cortical development characterized by overfolding and abnormal lamination of the cerebral cortex. Manifestations include epilepsy, speech disturbance and motor and cognitive disability. Causes include acquired prenatal insults and inherited and de novo genetic variants. The proportion of patients with polymicrogyria and a causative germline or mosaic variant is not known. The aim of this study was to identify the monogenic causes of polymicrogyria in a heterogeneous cohort of patients reflective of specialized referral services. Patients with polymicrogyria were recruited from two clinical centres in Australia and Belgium. Patients with evidence of congenital cytomegalovirus infection or causative chromosomal copy number variants were excluded. One hundred and twenty-three patients were tested using deep sequencing gene panels including known and candidate genes for malformations of cortical development. Causative and potentially causative variants were identified and correlated with phenotypic features. Pathogenic or likely pathogenic variants were identified in 25/123 (20.3%) patients. A candidate variant was identified for an additional patient but could not be confirmed as de novo, and therefore it was classified as being of uncertain significance with high clinical relevance. Of the 22 dominant variants identified, 5 were mosaic with allele fractions less than 0.33 and the lowest allele fraction 0.09. The most common causative genes were TUBA1A and PIK3R2 . The other eleven causative genes were PIK3CA, NEDD4L, COL4A1, COL4A2, GPSM2, GRIN2B, WDR62, TUBB3, TUBB2B, ACTG1 and FH . A genetic cause was more likely to be identified in the presence of an abnormal head size or additional brain malformations suggestive of a tubulinopathy, such as dysmorphic basal ganglia. A gene panel test provides greater sequencing depth and sensitivity for mosaic variants than whole exome or genome sequencing but is limited to the genes included, potentially missing variants in newly discovered genes. The diagnostic yield of 20.3% indicates that polymicrogyria may be associated with genes not yet known to be associated with brain malformations, brain-specific somatic mutations or non-genetic causes. Graphical Abstract: Abstract : Polymicrogyria is a common cortical malformation, yet genetic causes remain unclear. Stutterd et al. ascertained 123 patients for deep sequencing. Pathogenic variants were identified in 20.3% (25% mosaic). The two most commonly mutated genes were TUBA1A and PIK3R2. A genetic diagnosis found in ∼60% of patients with macrocephaly.